Combined full-length transcriptomic and metabolomic analysis reveals the regulatory mechanisms of adaptation to salt stress in asparagus - Zhang, Xuhong; Han, Changzhi; Liang, Yuqin; Yang, Yang; Liu, Yun; Cao, Yanpo (Frontiers in Plant Science, 2022)
Soil salinity is a very serious abiotic stressor that affects plant growth and threatens crop yield. Thus, it is important to explore the mechanisms of salt tolerance of plant and then to stabilize and improve crop yield. Asparagus is an important cash crop, but its salt tolerance mechanisms are largely unknown. Full-length transcriptomic and metabolomic analyses were performed on two asparagus genotypes: ‘jx1502’ (a salt-tolerant genotype) and ‘gold crown’ (a salt-sensitive genotype). Compared with the distilled water treatment (control), 877 and 1610 differentially expressed genes (DEGs) were identified in ‘jx1502’ and ‘gold crown’ under salt stress treatment, respectively, and 135 and 73 differentially accumulated metabolites (DAMs) were identified in ‘jx1502’ and ‘gold crown’ under salt stress treatment, respectively. DEGs related to ion transport, plant hormone response, and cell division and growth presented differential expression profiles between ‘jx1502’ and ‘gold crown.’ In ‘jx1502,’ 11 ion transport-related DEGs, 8 plant hormone response-related DEGs, and 12 cell division and growth-related DEGs were upregulated, while 7 ion transport-related DEGs, 4 plant hormone response-related DEGs, and 2 cell division and growth-related DEGs were downregulated. Interestingly, in ‘gold crown,’ 14 ion transport-related DEGs, 2 plant hormone response-related DEGs, and 6 cell division and growth-related DEGs were upregulated, while 45 ion transport-related DEGs, 13 plant hormone response-related DEGs, and 16 cell division and growth-related DEGs were downregulated. Genotype ‘jx1502’ can modulate K+/Na+ and water homeostasis and maintain a more constant transport system for nutrient uptake and distribution than ‘gold crown’ under salt stress. Genotype ‘jx1502’ strengthened the response to auxin (IAA), as well as cell division and growth for root remodeling and thus salt tolerance. Therefore, the integration analysis of transcriptomic and metabolomic indicated that ‘jx1502’ enhanced sugar and amino acid metabolism for energy supply and osmotic regulatory substance accumulation to meet the demands of protective mechanisms against salt stress. This work contributed to reveal the underlying salt tolerance mechanism of asparagus at transcription and metabolism level and proposed new directions for asparagus variety improvement.